Edukasi & Screening Masyarakat tentang Pencegahan Kanker dan Penyakit Mulut - Kartono, Faradhillah Kartono; zainuddin, sudirman; Zamli (Jurnal Makkareso, 2025)
Oral cancer is one of the preventable non-communicable diseases through education and early detection. Public awareness regarding the dangers of oral cancer and other oral diseases remains low, especially in the working area of the UPT Bajo Barat Community Health Center. This community service activity aimed to increase public knowledge about risk factors, early signs of oral cancer, proper oral hygiene techniques, and the importance of routine dental check-ups. The methods included interactive health education, practical toothbrushing demonstrations, and oral health screening. The education session was held on July 12, 2025, with 10 participants, followed by oral screenings and hygiene practices on July 14–18, 2025. Participants also received toothbrushes and toothpaste as incentives. The results showed that all participants understood the material and were highly enthusiastic about participating in the screening process. This activity had a positive impact on improving health literacy, strengthening the role of the community health center as a hub for health promotion, and served as a practical implementation of the university’s community service commitment. It is hoped that this program can be continued and expanded to reach broader community groups in the future.